10 điểm quan trọng trong khuyến cáo cập nhật về chẩn đoán và xử trí suy tim năm 2016 - Ban Thư ký (Tạp chí Tim mạch học Việt Nam, 2016)
10 điểm quan trọng trong khuyến cáo cập nhật về chẩn đoán và xử trí suy tim năm 2016